A presentation - Victory Studios, VS; Kilkenny Association, KILK
Colour group portrait photograph showing a man and a woman holding up an unidentified object, in front of another man in clerical dress. Mounted in a 'Mecca Banqueting Halls' card folder. Photograph by Victory Studios, copyright Victory Studios.